Specific Mixing Energy of Cemented Paste Backfill, Part I: Laboratory Determination and Influence on the Consistency - Reagan Kabanga Dikonda (MDPI AG, 2021)
Slump determination is widely used to assess the consistency and transportability of fresh cemented paste backfill (CPB). CPB consistency can depend on the mixing procedure for CPB preparation. In this paper, a method was developed to determine the specific mixing energy (SME) that is dissipated during the preparation of CPB mixtures and to analyze its effect on CPB consistency. For this purpose, CPB recipes were prepared using two tailings and the mixing parameters (mixing time and speed and load mass) were successively varied. SME was determined for each mixture using a power meter equipped with an energy recording system mounted on a laboratory Omcan mixer. Slump was also determined for each mixture. A semi-empirical model was then developed to predict SME as a function of the mixing parameters. Results showed that predicted SME compared well with measured SME during CPB preparation. Results also showed that slump increased with increasing SME. The influence of SME on the rheological and mechanical properties of CPB and practical applications are presented in a companion paper.